Excavations at Haft Tepe, Iran - Negahban, E.O. (1991)
esp. pp.49-101: Seals and Seal Inscriptions; pp. 102-112: Stelae, Inscriptions, and Tablets; Haft Tepe = mE Ka-ab-na-a[k], nA Ka-pi-in-ak/Kapnak?